Soil Texture and organic carbon fractions in arid-semiarid soils of Argentina - Schiavi Catril, Mirko Israel (2018)
Fil: Schiavi Catril, Mirko Israel. Universidad Nacional de Río Negro. Río Negro; Argentina.